Pengaruh Religiusitas Budaya Etis Organisasi, dan Gaya Hidup Terhadap Fraud di Tempat Kerja - Fakhriyadi, Muhammad (Jurnal Ilmiah Mahasiswa FEB, 2017)
Fraud is caused by two factors, i.e. internal and external factors. This research uses those factors as the independent variables. Religiosity and lifestyle represent the internal factors, and organization ethical culture represents the external factor. This research tries to identify the influence of religiosity, lifestyle, and organization ethical culture on fraud in the workplace. Fraud triangle is used as the basic and the main theory of this research. Through non-probability convenience sampling, 90 employees of oil and gas company are selected to be the respondents. The data are analyzed through multiple linear analysis using SPSS 23. This study finds that religiosity and organization ethical culture, respectively, have negative influence on fraud in the workplace. The respondents have high religiosity values. They try to produce and keep good behaviors. They also believe that God watches over them. Furthermore, there is established organization ethical culture in the company since the company has successfully communicated the company's ethical codes to the employees. Lifestyle has a positive influence on fraud in the workplace. Almost all of the respondents classified as non-spendthrift people, and they feel contented with the money they earn. The implications of this study are that fraud prevention does not only rely on external supervision, that it needs the internalization of religiosity values, and that ethical condition building in the workplace is necessary to make employees have integrity in their performance.Keywords: religiosity, organization ethical culture, lifestyle, fraud